Wildlife Is Overlooked in the Epidemiology of Medically Important Antibiotic-Resistant Bacteria - Dolejska, Monika; Literak, Ivan (Antimicrobial agents and chemotherapy, 2019)
Wild animals foraging in the human-influenced environment are colonized by bacteria with clinically important antibiotic resistance. The occurrence of such bacteria in wildlife is influenced by various biological, ecological, and geographical factors which have not yet been fully understood. More research focusing on the human-animal-environmental interface and using novel approaches is required to understand the role of wild animals in the transmission of antibiotic resistance and to assess potential risks for the public health.
Keywords: Bacteria; wild animal; Animals; beta-Lactamases; Drug Resistance, Bacterial; bakteriální proteiny; Humans; transmission; beta-laktamasy; Bacterial Proteins; Microbial Sensitivity Tests; Animals, Wild; Anti-Bacterial Agents; environment; landfill; zvířata; carbapenemase; antibiotics; divoká zvířata; bakteriální léková rezistence; lidé; mikrobiální testy citlivosti; antibakteriální látky